Transcendental Reelism - Kent, Laurence (Transformations, 2024)
Theories surrounding the spiritual aspects of cinema often utilise a concept of the transcendental, exploring film’s ability to transcend its worldly material. However, this equation of the transcendental and the transcendent evades an important moment in the history of philosophical idealism that sought to distinguish such terms. Immanuel Kant interjected into the tradition of dogmatic idealism with his own “transcendental idealism”: a move away from a metaphysics of things-in-themselves towards the transcendental schema that makes thinking possible in the first place. It is then Gilles Deleuze that takes the transcendental to bare on a taxonomy of cinema, utilising a reorientation of Kant’s critical project in the form of transcendental empiricism, an immanent and material positing of the schema of real experience. This article will expound further upon what the immanent transcendental can mean for an understanding of film by comparing the cinematic mechanism with the machinery of the transcendental, first by modelling the two against each other, seeing Kant’s transcendental framework as proto-cinematic, and then by thinking materially across the two domains through their historicity and technicity.